Relationships between Fluoride Intake, Urinary Fluoride Excretion and Fluoride Retention in Children and Adults: An Análisis of Available Data (2010)
ABSTRACT: The aim of this study was to examine the relationship between total daily fluoride intake (TDFI), daily urinary fluoride excretion (DUFE) and fractional fluoride retention (FFR) using available data, in order to clarify the ability of DUFE to predict TDFI and, therefore, the risk of fluorosis development. Examination of published reports of simultaneous measurement of TDFI and DUFE, together with data from two unpublished Chilean studies, yielded data for 212 children aged less than 7 years and for 283 adults aged 18–75 years, providing a total of 212 and 269 data points, respectively. The relationship between DUFE and TDFI was studied for children and adults, separately. Daily fluoride retention (DFR) was estimated as a function of TDFI in children and adults assuming an average 90% fluoride absorption, and the numerical relationships between the estimated FFR and the TDFI were explored. Limiting FFR values of 0.55 and 0.36 were found for children and adults, respectively, above a threshold of TDFI of 0.5 and 2 mg, respectively. Neutral fluoride balances were predicted when the TDFI was equal to approximately 0.07 mg F/day for children and 0.8 mg F/day for adults. For children and adults, it is possible to obtain reasonably good estimations of community-based TDFI and DFR, using DUFE data. The advantages and limitations of these relationships, together with the need for future studies, are discussed.